Effect of whole-day work on surgical performance during simulated laparoscopic surgery: study protocol for a controlled cross over laboratory trial - Sevestre, Anaïs; Souron, Robin; Deschamps, Thibault; Sarcher, Aurélie; Thubert, Thibault; Dochez, Vincent (Frontiers in Public Health, 2024)
Introduction Laparoscopy has become a fundamental aspect of surgery, presenting new challenges such as fatigue, encompassing both muscular and cognitive components. Given its potential to affect surgical precision and create difficulties for the surgeon, it is crucial to study the mechanisms of fatigue for patient safety and the well-being of surgeons. This study aims to demonstrate the influence of general fatigue on surgeons’ performance, incorporating assessments of movement quality through balance, kinematics, and muscle activation, as well as perceived workload. Additionally, the study seeks to evaluate how surgeons’ experience may affect fatigue outcomes. Methods and analysis A controlled cross-over laboratory trial involving 29 residents and surgeons from the obstetrics and gynecology department of Nantes University Hospital is underway. Recruitment started in March 2023 and ended in September 2023. Participants with varying levels of experience perform two one-hour sessions of training box exercises, one in the morning (control condition) and the other at the end of a workday. The primary outcome is a composite score derived from the time to complete the Suturing and Knot Tying Training and Testing (SUTT) exercise, along with the number and quality of stitches. Secondary outcomes include perceived fatigue, discomfort, physical strain, muscle tension, mental workload, muscle activation (measured by surface electromyography), balance (measured using a force platform), and kinematics (measured using motion capture). Ethics and dissemination The study received ethical approval from the local ethics committee CERNI in December 2022 (n°13,122,022). Results will be presented in international conferences, submitted to peer-reviewed journals, and serve as a feasibility study for subsequent publications.